Morphology of polystyrene/poly(methyl methacrylate) blends: Effects of carbon nanotubes aspect ratio and surface modification. Issue 10 (16th July 2015) - Guo, Jiaxi; Briggs, Nicholas; Crossley, Steven; Grady, Brian P.
<x xml:space="preserve">Abstract</x> Multiwalled carbon nanotubes (MWCNTs) with aspect ratios (ARs) ranging from 94 to 474 were incorporated into polystyrene (PS)/poly(methyl methacrylate) blends using solution mixing and melt mixing. Also, two functionalized MWCNTs were prepared from the nanotubes having AR 94: one was oxidized by nitric acid while the other was further modified with amine‐terminated PS attached to carboxyl groups to form amides. The two functionalized MWCNTs (1 wt %) were used to show that which phase the carbon nanotubes (CNTs) were located in could be controlled with nanotube surface chemistry. When nanotubes were confined to the minor phase, the size of the minor domain first decreased with adding low AR CNT as expected due to the increased viscosity of the minor phase. However, at higher ARs, the size increased beyond the size for the minor domain with no nanotubes, and at high enough AR, the shape of the minor domain changed from spherical to an elongated irregular shape. © 2015 American Institute of Chemical Engineers AIChE J, 61: 3500–3510, 2015